A Geospatial Appraisal of Oil Spill Health Impacts: A Niger Delta Case Study - Chijioke I. Anyanwu; James K. Lein (Journal of Basic & Applied Sciences, 2019)
Oil spills resulting from pipeline breakages and operational failures during oil exploration have increased in prevalence in the Niger Delta, with more than 8,000 spills occurring over the past decade. Previous research has linked oil spills to human health hazards such as derma-toxic diseases, and various cancers. However, few studies have considered the health effects of oil spills on maternal and child health. This study seeks to fill this gap in literature by focusing on infant diarrhea in the Niger Delta. Diarrheal diseases account for 1 in 9 child deaths worldwide, making diarrhea the second leading cause of death among children under the age of five. Defining the spatio-temporal pattern of infant diarrhea and its relationship to oil spill contamination is critical in understanding mortality risk and enabling policy decisions aimed at reducing infant mortality rates in the region. Despite substantial data limitations, geospatial analysis revealed a statically significant spatial clustering of oil spill incidence and infant diarrhea: a pattern strongly correlated with spatial proximity to rural, low-income households with limited access to improved water sources and sanitation facilities. These locations evidenced higher rates of diarrhea incidence consistently across the region.